2012
DOI: 10.1364/boe.3.001757
|View full text |Cite
|
Sign up to set email alerts
|

Generalized cell morphological parameters based on interferometric phase microscopy and their application to cell life cycle characterization

Abstract: We present analysis tools which are formulated using wide-field interferometric phase microscopy measurements, and show their ability to uniquely quantify the life cycle of live cancer cells. These parameters are based directly on the optical path delay profile of the sample and do not necessitate decoupling the refractive index and the thickness in the cell interferometric phase profile, and thus can be calculated using a single-frame acquisition. To demonstrate the use of these parameters, we have constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(135 citation statements)
references
References 27 publications
7
127
0
1
Order By: Relevance
“…The ability to measure cell count was validated for the first time in 2008 by Mölder et al [21], using human breast and prostate cancer cell lines, as well as a mouse fibroblast cell line. Measurement of cell growth has been well documented for both adherent and non-adherent cells [8,9,15,[25][26][27][28]47,49,56,59,61]. By segmentation of cellular outlines, morphology and motility can also be studied [7,50,51,57,80].…”
Section: Principles Of Qpimentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to measure cell count was validated for the first time in 2008 by Mölder et al [21], using human breast and prostate cancer cell lines, as well as a mouse fibroblast cell line. Measurement of cell growth has been well documented for both adherent and non-adherent cells [8,9,15,[25][26][27][28]47,49,56,59,61]. By segmentation of cellular outlines, morphology and motility can also be studied [7,50,51,57,80].…”
Section: Principles Of Qpimentioning
confidence: 99%
“…Cell death and cell proliferation are stringently controlled by the cell cycle, and studies have shown the ability of QPI to identify the different phases of the cell life cycle, i.e., specific changes in cell phase correlating to either a G1 or a G2/M arrest [13,25,38,44,57,89]. Kamlund et al constructed individual cell trees showing the way in which the drug salinomycin affects individual cells cultured in normoxia or hypoxia, by monitoring the times to first and last division [13].…”
Section: Cell Death Studies With Qpimentioning
confidence: 99%
“…33 It has been shown that the measured phase in the image corresponds to the dry mass density distribution within the cell. 26,27 In contrast to existing DHM techniques, 4,7,18,19 the use of incoherent illumination enables high-quality quantitative phase imaging with strong suppression of coherent noise and parasitic interferences while providing high temporal stability and spatial uniformity of the phase measurement. 25 Using the approach described in Ref.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Cell life cycle characterization by monitoring of morphometric (MO) and quantitative phase features was proposed in Ref. 18. Assessment of wound healing by monitoring the cellular volume, dry mass, and refractive index was presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Similar multiparameter approaches have been previously utilized to characterize phase distortions in tissue sections, 14 red blood cells, 24 phase fluctuations observed in waves transmitted through cells, 16 and in the context of monitoring the cell cycle through phase-derived parameters. 25 Our approach is the first to investigate the interdependence of these parameters.…”
Section: Introductionmentioning
confidence: 99%